Kinetic Evolution of Laser Ablating Alloy Materials - Wang, Junxiao; Zhao, Yang; Zhang, Lei; Wang, Shuqing; Su, Maogen; Sun, Duixiong; Min, Qi; Ma, Weiguang; Yin, Wangbao; Jia, Suotang (Frontiers in Physics, 2021)
Through the theoretical simulation and analysis of the whole process of laser ablating target and producing plasma with high spatio-temporal resolution, it is helpful for people to gain a more complete understanding of the ablation process of target and the evolution process of plasma parameters, which has an important guiding role for the improvement and optimization of laser ablation technology. Alloys are commonly used in daily life, but there are few researches on laser-induced alloy targets at present. Therefore, based on the thermal model of laser ablation and the two-dimensional axisymmetric multi-species hydrodynamic model, the process of laser ablating Al-Mg alloy under atmospheric pressure argon is theoretically simulated, and the ablation process of alloy target and the spatio-temporal evolution results of plasma parameters under different laser irradiances are compared. At high laser irradiance, the melt and evaporation depth, laser energy absorption and plasma characterization parameters are much greater than those at low laser irradiance, and the species energy distribution at different laser irradiance also presents different trends. In addition, the velocity of different species is calculated according to the position-time diagram of the maximum emission intensity, and they expand at a constant speed during the studied time. These results can provide some theoretical guidance for the early application of laser-induced breakdown spectroscopy in metallurgy.